Feedbacks link ecosystem ecology and evolution across spatial and temporal scales: Empirical evidence and future directions. (21st January 2019) - Ware, Ian M.; Fitzpatrick, Connor R.; Senthilnathan, Athmanathan; Bayliss, Shannon L. J.; Beals, Kendall K.; Mueller, Liam O.; Summers, Jennifer L.; Wooliver, Rachel C.; Van Nuland, Michael E.; Kinnison, Michael T.; Palkovacs, Eric P.; Schweitzer, Jennifer A.; et al.
Abstract: Unifying ecosystem ecology and evolutionary biology promises a more complete understanding of the processes that link different levels of biological organization across space and time. Feedbacks across levels of organization link theory associated with eco‐evolutionary dynamics, niche construction and the geographic mosaic theory of co‐evolution. We describe a conceptual model, which builds upon previous work that shows how feedback among different levels of biological organization can link ecosystem and evolutionary processes over space and time. We provide empirical examples across terrestrial and aquatic systems that indicate broad generality of the conceptual framework and discuss its macroevolutionary consequences. Our conceptual model is based on three premises: genetically based species interactions can vary spatially and temporally from positive to neutral (i.e. no net feedback) to negative and drive evolutionary change; this evolutionary change can drive divergence in niche construction and ecosystem function; and lastly, such ecosystem‐level effects can reinforce spatiotemporal variation in evolutionary dynamics. Just as evolution can alter ecosystem function locally and across the landscape differently, variation in ecosystem processes can drive evolution locally and across the landscape differently. By highlighting our current knowledge of eco‐evolutionary feedbacks in ecosystems, as well as information gaps, we provide a foundation for understanding the interplay between biodiversity and ecosystem function through an eco‐evolutionary lens. A plain language summary is available for this article. Abstract : Plain Language Summary